Skill formation in cross-border contexts : the case of the trinational Upper Rhine region - Graf, Lukas [Verfasser] (My University, 2020)
"Cross-border regions display significant economic, political, and cultural cooperation and represent a central feature of Europe - not least as innovation labs for the European integration project. A key example is the trinational French-GermanSwiss Upper Rhine region. Each of the respective bordering countries displays a specific mode of regulation in VET. How do actors govern vocational education and training (VET) in this dynamic industry cluster in which distinct national political-administrative units do not overlap with the functional needs of employers and (future) employees? Relying on expert interviews and document analysis, this chapter offers a novel comparison of the respective subnational units within each cross-border region. The institutional study finds a key pattern through which skill formation is institutionalised within the cross-border context: the leveraging of complementarities between distinct educational institutions. In combining the specific strengths of different national skills regimes, VET stakeholders in cross-border regions are in a position to enlarge the scope and capacities of their skill regime far beyond national borders." (author's abstract ; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; G 1.2.3 Qualifikationsentwicklungen; I 2.2.1 Westeuropa; I 2.1 Deutschland; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Grenzüberschreitende Zusammenarbeit; Kompetenzentwicklung; Qualifikationsbedarf; Qualifikationsentwicklung; Arbeitsmarkt; Schweiz; Frankreich; Bundesrepublik Deutschland; Rhein